2015
DOI: 10.1038/srep16147
|View full text |Cite|
|
Sign up to set email alerts
|

Lactobacillus rhamnosus GG Lysate Increases Re-Epithelialization of Keratinocyte Scratch Assays by Promoting Migration

Abstract: A limited number of studies have investigated the potential of probiotics to promote wound healing in the digestive tract. The aim of the current investigation was to determine whether probiotic bacteria or their extracts could be beneficial in cutaneous wound healing. A keratinocyte monolayer scratch assay was used to assess re-epithelialization; which comprises keratinocyte proliferation and migration. Primary human keratinocyte monolayers were scratched then exposed to lysates of Lactobacillus (L) rhamnosus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
68
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(86 citation statements)
references
References 34 publications
5
68
0
1
Order By: Relevance
“…A cell monolayer scratch assay is used to assess re-epithelialization [40]. In the present study, we demonstrated a large induction of cell migration in gingival epithelial cells by rHMGB1 during wound scratch assay after 24–48 h. This finding is consistent with previous report that HMGB1 is a potent cell migration and proliferation promoting agent [41].…”
Section: Discussionsupporting
confidence: 93%
“…A cell monolayer scratch assay is used to assess re-epithelialization [40]. In the present study, we demonstrated a large induction of cell migration in gingival epithelial cells by rHMGB1 during wound scratch assay after 24–48 h. This finding is consistent with previous report that HMGB1 is a potent cell migration and proliferation promoting agent [41].…”
Section: Discussionsupporting
confidence: 93%
“…The rationale for these strains was based on their genome availability 22-24 , knowledge of their host interaction capacity 25,26 , their robustness and growth capacity 22,24,26 ( Extended Data Figure 2a) , in addition to information on their safety in humans after oral 27,28,29 , nasal 30 and vaginal 31 high-dose application. L. rhamnosus GG was also selected because of previous reports on its capacity to inhibit the toxic effects of S. aureus on epidermal keratinocytes 32 , its strain-dependent capacity to promote re-epithelialization 33 and to augment tight-junction barrier function in human primary epidermal keratinocytes 34 , and our previous experience with this probiotic strain 25 . For microbiome modulation, C. acnes was targeted as model pathobiont associated with the inflammatory character of acne vulgaris.…”
Section: Resultsmentioning
confidence: 99%
“…25 Furthermore, the integrity of epithelial cells isolated from the female genital tract was directly disrupted by the presence of HIV-1. 27 Re-epithelialization, the migration and proliferation of epithelial cells, 28 is an important step of mucosal wound repair, as well as that of skin and other tissues, sealing the epithelial defect and restoring barrier integrity. 27 Re-epithelialization, the migration and proliferation of epithelial cells, 28 is an important step of mucosal wound repair, as well as that of skin and other tissues, sealing the epithelial defect and restoring barrier integrity.…”
mentioning
confidence: 99%
“…28,[38][39][40] On the other hand, L. salivarius and L. plantarum inhibited oral epithelial wound healing 41. A recent study showed that a bioengineered L. reuteri with a plasmid encoding CXCL12 accelerated cutaneous wound healing in mouse, while nontransformed L. reuteri delayed wound closure 42.…”
mentioning
confidence: 99%
See 1 more Smart Citation